Abdominal Lymph Node Metastasis in Patients With Non-Small-Cell Lung Cancer as Shown by PET/CT - Karyagar, Savas; Koc, Zehra Pinar; Karyagar, Sevda S.; Ozturk, Ibrahim; Cengiz, Ercument; Sayici, Yasin; Balci, Tansel Ansal (Lippincott Williams & Wilkins, 2013)
Purpose: The aim of this study is to investigate the frequency and the spread of abdominal lymph node metastasis in patients with non-small-cell lung cancer (NSCLC) by F-18-FDG PET/CT. Patients and Methods: Retrospective evaluation of the F-18-FDG PET/CT examinations of 1191 patients diagnosed with NSCLC was performed. The metastatic abdominal lymph nodes of the patients were classified as inside the routine imaging field (covering the field of chest CT including adrenal glands) and outside the field. Results: Seventy-four patients (6 F, 68 M; mean: 61 +/- 11 years old) among 1191 patients (6%) were identified to have abdominal lymph node metastases. These abdominal lymph node metastasis changed management in 10 out of 74 patients (14%), and there were lymph node metastases outside the routine conventional imaging field in 43 (58%) patients. Conclusion: F-18-FDG PET/CT provided identification of the distant metastatic lymph nodes out of conventional imaging field in more than half of NSCLC patients with abdominal metastasis which changed patient management in 14% of the patients due to abdominal lymph node metastasis outside the routine imaging field. This study shows the necessity of imaging NSCLC patients with an imaging protocol with larger imaging field like PET/CT.
Keywords: abdominal lymph nodes; non-small-cell lung cancer; FDG; PET/CT